Marketing internetowy w korporacji międzynarodowej - studium przypadku firmy Nestle - Pizło, Wojciech (Internet Marketing in International Corporation - Case Study of Nestle Enterprise, 2006)
The paper presents the use of Internet in marketing actions in Nestle Poland enterprise. The development of Internet marketing and an action in integrated Internet marketing tools is shown in the paper. In the end of the paper it presents a relationship between classical marketing and Internet marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 234-241